Synthesis of metal organic framework (MOF-199) coated with cellulose nanocrystal - Ghaemi, Ferial; Amri, Mohamad Ridzuan; Abdullah, Luqman Chuah (2018)
The hybrid material of a copper-based metal-organic framework (MOF-199) and cellulose nanocrystal (CNC) was explored in this research. A highly porous MOF-199 was synthesized from the reaction of copper nitratetrihydrate and 1,3,5-benzenetricarboxylic acid by solvothermal method, and CNC was produced by combination method of chemical hydrolysis and mechanical treatment to reach high purity CNC with uniform shape. Physical characterizations of the MOF-199, CNC and MOF-199/CNC were achieved by using avariety of different techniques, including scanning electron microscope (SEM), transmission electron microscopy (TEM), BET surface area. Based on the results by coating CNC on the surface of MOF-199, the porosity of the product increases significantly.